Cardiovascular magnetic resonance imaging of scar development following pulmonary vein isolation: a prospective study. - Jeff Hsing; Dana C Peters; Benjamin R Knowles; Warren J Manning; Mark E Josephson (PLoS ONE, 2014)
Cardiovascular magnetic resonance (MR) provides non-invasive assessment of early (24-hour) edema and injury following pulmonary vein isolation (by ablation) and subsequent scar formation. We hypothesize that 24-hours after ablation, cardiovascular MR would demonstrate a pattern of edema and injury due to ablation and the severity would correlate with subsequent scar.Fifteen atrial fibrillation patients underwent cardiovascular MR prior to pulmonary vein isolation, 24-hours post (N = 11) and 30-days post (N = 7) ablation, with T2-weighted (T2W) and late gadolinium enhancement (LGE) imaging. Left atrial wall thickness, edema enhancement ratio and LGE enhancement were assessed at each time point. Volumes of LGE and edema enhancement were measured, and the circumferential presence of injury was assessed at 24-hours, including comparison with LGE enhancement at 30 days.Left atrial wall thickness was increased 24-hours post-ablation (10.7 ± 4.1 mm vs. 7.0 ± 1.8 mm pre-PVI, p<0.05). T2W enhancement at 24-hours showed increased edema enhancement ratio (1.5 ± 0.4 for post-ablation, vs. 0.9 ± 0.2 pre-ablation, p < 0.001). Edema and LGE volumes at 24-hours were correlated with 30-day LGE volume (R = 0.76, p = 0.04, and R = 0.74, p = 0.09, respectively). Using a 16 segment model for assessment, 24-hour T2W had sensitivity, specificity, and accuracy of 82%, 63%, and 79% respectively, for predicting 30-day LGE. 24-hour LGE had sensitivity, specificity, and accuracy of 91%, 47%, and 84%.Increased left atrial wall thickening and edema were characterized on cardiovascular MR early post-ablation, and found to correlate with 30-day LGE scar.